A hierarchical carbon nanotube forest supported metal phosphide electrode for efficient overall water splitting. Issue 2 (22nd December 2020) - Wang, Zuohui; Wei, Chengyu; Zhu, Xuebing; Wang, Xiaobing; He, Jinling; Zhao, Yong
Abstract : Metal phosphides on self-supportive CNT forest materials with a hierarchical branched architecture have abundant active sites and excellent electrical conductivity, providing an effective strategy for preparing efficient OER and HER electrodes. Abstract : Transition metal phosphides (TMPs) have become one type of promising hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) catalyst in alkaline medium; however, the low amount of metal active sites and the poor electronic conductivity of TMPs have become the limiting factors for achieving high-performance TMP based electrocatalysts. Herein, a hierarchical carbon nanotube (CNT) forest was used to load TMP materials to form self-supported electrodes (NiCoP-CNT@NiCo/CP and NiFeP-CNT@NiCo/CP), guaranteeing catalytic electrodes with a high amount of metal sites and excellent electronic conductivity. As expected, the electrodes display low overpotentials of 82 and 230 mV at a current density of 10 mA cm −2 for the HER and OER in alkaline solutions, respectively. Moreover, the overall water electrolyzer assembled with NiCoP-CNT@NiCo/CP as a cathode and NiFeP-CNT@NiCo/CP as an anode exhibits superior electrolysis performance (1.58 V/10 mA cm −2 ). The remarkable performance is attributed to the unique hierarchical CNT forest architecture of the as-prepared catalytic electrodes and the synergistic effect between TMP nanoparticles and CNTs.